Young people’s support for the Finns Party: An incomplete story - Hansen, Michael A. (Valtiotieteellinen yhdistys, 2025)
The narrative that Finns Party support is substantial among young people is misleading. Age plays only a limited role in determining support for the party. The real puzzle is the substantial age gap in support for the Social Democrats.